1987
DOI: 10.7863/jum.1987.6.5.225
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic anatomy of the larynx, with particular reference to the vocal cords.

Abstract: Sonographic images of the vocal cords were obtained in 41 healthy human subjects using a phased array realtime ultrasound scanner. The thyroid cartilage provides the acoustic window for sonographic visualization of the vocal cords. The false vocal cords appear as hyperechoic structures, while the true vocal cords are seen as hypoechoic structures. The symmetry of movement of the vocal cords during respiration becomes apparent on examination in real time. Sonography may prove to be a potentially useful techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 0 publications
0
55
0
3
Order By: Relevance
“…The difficulty in defining the relationship between laryngotracheal injury and post-extubation stridor is that the presence of the endotracheal tube precludes direct visualisation of the upper airway, prior to extubation. Other noninvasive approaches to examine the VC and the larynx would be helpful and there have been many ultrasonographical methods developed for visualising these [8][9][10][11][12][13][14]. Moreover, the current authors found that the motion of the VC, caused by air passage during respiration, could also be demonstrated using ultrasound (US).…”
mentioning
confidence: 88%
“…The difficulty in defining the relationship between laryngotracheal injury and post-extubation stridor is that the presence of the endotracheal tube precludes direct visualisation of the upper airway, prior to extubation. Other noninvasive approaches to examine the VC and the larynx would be helpful and there have been many ultrasonographical methods developed for visualising these [8][9][10][11][12][13][14]. Moreover, the current authors found that the motion of the VC, caused by air passage during respiration, could also be demonstrated using ultrasound (US).…”
mentioning
confidence: 88%
“…As most sound waves are reflected at inter faces with cartilage or air, intralaryngeal structures are obscured. Recent studies, however [5][6][7], clearly demon strated that ultrasound may visualize, e.g., thyroid carti lage invasion and advanced laryngeal cancer. The present study is to our knowlege the first to describe the sono graphic appearance of laryngoceles.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies deal with the evaluation of (intra-)laryngeal structures by real-time ultrasound [5][6][7], Ultrasound is hampered by the (partly) mineralized cartilage of the larynx and the air in the airway. As most sound waves are reflected at inter faces with cartilage or air, intralaryngeal structures are obscured.…”
Section: Discussionmentioning
confidence: 99%
“…6 Sonographic examination of the larynx is an easy and useful imaging modality in infants. 2,7,8 It allows a good analysis of the cartilaginous structures, muscles, and endolaryngeal structures. 7,8 As observed in this case, ultrasonography appears to be useful for the differential diagnosis of rare causes of stridor in an ill premature baby.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 It allows a good analysis of the cartilaginous structures, muscles, and endolaryngeal structures. 7,8 As observed in this case, ultrasonography appears to be useful for the differential diagnosis of rare causes of stridor in an ill premature baby. In our case, ultrasonography was able to diagnose rapidly the cystic nature of the laryngeal mass, identify its precise location, and confirm the existence of suspected recurrence after initial limited endoscopic treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%